Enterprise experiences in the culture of new sparids - Bodington P. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
Demand is steadily increasing for hatchery production of alternative species to sea bass, Dicentrarchus labrax, and sea bream, Sparus aurata. Production of these 'new' species is dependent on biological factors such as egg production efficiency, larval survival, fry growth rates, deformity levels, disease tolerance, handling tolerance, as well as non-biological factors like the certainty of fry demand and confidence in meeting production targets for the standard species. These factors vary with hatchery site and design as well as target market. This paper summarises experiences in hatchery production of Puntazzo puntazzo, Diplodus sargus, Dentex dentex and Pagrus pagrus.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)